Edukasi Perawatan Kaki pada Penderita Diabetes Melitus Tipe II Sebagai Upaya Pencegahan Ulkus Kaki Diabetes Melitus di Puskesmas Purwokerto Barat - Johany Nia Julianda; Suci Khasanah; Indah Susanti (Pusat Riset dan Inovasi Nasional, 2025)
Diabetes mellitus (DM) is a chronic metabolic disease characterized by the body's inability to metabolize glucose, fat, and protein due to a lack of insulin or insulin resistance. This condition causes hyperglycemia, which carries the risk of various complications, one of which is diabetic foot ulcers. These complications often have serious consequences and can even lead to amputation if not properly treated. Therefore, the principles of foot examination and care are crucial aspects that must be understood and carried out routinely by DM sufferers, especially in developing countries like Indonesia, which have a relatively high diabetes prevalence. Based on the results of a pre-survey conducted at the West Purwokerto Community Health Center on Thursday, August 22, 2024, it was found that 10 DM sufferers were at risk of developing diabetic foot disease. This condition emphasizes the importance of foot care education for the community, especially DM sufferers. This Community Service (PkM) activity aims to increase the knowledge, skills, and awareness of DM sufferers regarding the importance of foot care as a preventative measure against diabetic ulcers. The methods used in this PkM activity include lectures, interactive discussions, and question-and-answer sessions. The educational media used were PowerPoint presentations, leaflets, and educational videos to convey information more clearly and easily understood. The activity was carried out in two meetings involving 30 participants with diabetes. The evaluation results showed a significant increase in knowledge, where the average value before education was 57.13%, increasing to 80.46% after education was provided. Overall, this activity succeeded in increasing participants' understanding of foot care and preventing diabetes complications. The results of this community service will then be published in the Community Service (PkM) journal and submitted as Intellectual Property Rights (IPR) in the form of an educational video.